Tradisionele geloof - Dreyer, W. A. (Hervormde teologiese studies, 1995)
Traditional belief Traditional belief is still very strong among black South Africans. Many Christians not only believe in Christ, but also in the spirits of the fore-fathers. The question arises as to how the relationship between traditional belief and christian faith must be seen. It also poses problems to the church in South Africa, which is mainly orientated to the theology of Western Europe. Proclaiming the gospel in a traditional situation will only be effective if traditional beliefs are taken into consideration. This article uses oral tradition as a source of information.